"Finding the Other Half of Me": Culture-Based Approaches to Music Education in Hawaiʻi. (April 2022) - Fitzpatrick, Kate R.
The purpose of this study was to examine how Hawaiian music teachers describe their uses of Hawaiian culture–based educational approaches in the music classroom. The theoretical lens of culture-based education framed the study in that it emphasizes increased attention to questions of cultural restoration within Indigenous communities. A collective descriptive case-study design was used to illuminate the complexities and particularities of the phenomenon of Hawaiian culture–based education utilized by four participant music teachers in their own particular contexts. Data collection included three interviews with each teacher participant, a student focus group interview at each school site, and field notes taken from in-person observations of each music classroom. Analysis revealed four themes central to the participants' experiences, including teachers' diverse approaches to culture-based education, their sources of cultural understanding, how they addressed or navigated challenges, and the multiple layers of meaning that they and their students derived from these culture-based approaches. Particularly compelling were findings related to each teacher's identity and relationship to Hawaiian culture, complicated issues of authenticity related to performing and teaching Hawaiian music, and the centrality of positive relationships to culture-based approaches.